DAMPAK PANDEMI COVID 19 TERHADAP PERGERAKAN INDEKS SAHAM: STUDI KASUS PASAR SAHAM SYARIAH INDONESIA - nurfitri martaliah; Salmia Salmia; Puji Wahyuli; Muhammad Habibullah Aminy; Ahmad Suhendri (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
The Islamic capital market is one of the financial investment instruments that alsoserves to meet the needs of Muslim investors to invest according to sharia in a country. TheIslamic capital market in recent years has experienced quite good growth in Indonesia,with various instruments in accordance with the needs and desires of the majority ofMuslims, and has the opportunity to create a fair redistribution of the income and wealthecosystem. But there are pandemic cases that occur 19 so that all financial and economicinstruments face obstacles including the Islamic capital market. This study aims to look atthe impact of a pandemic on the movement of Islamic stock indexes in Indonesia using aliterature study approach or looking for primary information from capital marketdevelopment data that is released regularly on the official website and also informationfrom other media. The results of research analysis by looking at data and analysis of othersimple trends conclude that in the following months during the covid pandemic 19 willcontinue to decline in the movement of stock indexes, if the covid 19 pandemic problem isnot resolved properly, stock movements will decline and endanger the Indonesian economy.So there is no concrete need to overcome this problem so that it does not become aneconomic recession.